The text of Marcion's gospel - Roth, Dieter T. (New Testament tools, studies and documents, 2015)
Preliminary Material -- 1 Introduction -- 2 History of Research -- 3 Sources and Methodology -- 4 Tertullian as a Source: Multiple Citations -- 5 Tertullian as a Source: Citations only in Adversus Marcionem -- 6 Epiphanius as a Source -- 7 The Adamantius Dialogue as a Source -- 8 Additional Sources -- 9 The Reconstruction of Marcion’s Gospel -- 10 Initial Conclusions and Avenues for Future Research -- Bibliography -- Indexes.